Physical property changes in commercial natural rubbers during long term storage - Jintana Yunyongwattanakorn (2018)
The physical properties during long term storage of selected commercial Standard Thai Rubbers (STR), i.e. STR XL, STR 5L and STR CV60 as high-graded natural rubber (NR), were investigated. Sections of commercial NR were subjected to examination after storage-hardening. STR 5L showed clearly an increase in Mooney viscosity (VR), Mooney relaxtion (MR30), gel content and initial plasticity (P0), higher than that of STR XL. This result suggests that STR 5L exhibits the highest inconsistency in physical properties. The increasing viscosity and gel content of STR 5L and STR XL samples suggest the occurrence of a crosslink structure during storage. STR CV60, known as a viscosity-stabilized NR sample, also showed an increase in VR, gel content, P0and high PRI value during long storage. These findings indicate that storage-hardening occurred in the rubber samples even after carefully controlled production procedures. As for the different sections of samples, there was no clear relation with gel content with respect to storage time, indicating that depth or positions of specimens in a certain rubber bale did not affect the storage-hardening phenomenon.